Analisis Cerpen Lelaki Yang Menderita Bila Dipuji Karya Ahmad Tohari Menggunakan Pendekatan Objektif dan Mimetik - Dzira Auliya Marsela; Muhamad Ansor (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
This research focuses on analyzing the short story "The Man Who Suffers When He is Praise" by Ahmad Tohari with an objective and mimetic approach, and using qualitative descriptive methods. The data source used is the short story "The Man Who Suffers When He is Praise" by Ahmad Tohari which was analyzed carefully and critically. Through an objective approach, this research aims to identify intrinsic elements such as theme, point of view, plot, setting, characters, characterization, language style and message in short stories. Meanwhile, a mimetic approach is used to find social elements in short stories that can be connected to the reality of everyday life. It is hoped that this research can encourage a deeper understanding of Ahmad Tohari's literary works and broaden readers' perspectives on the meaning of this short story in a social context. It is hoped that the results of this research will provide a more comprehensive insight into the quality of literature and the social message conveyed through the short story "The Man Who Suffers when He is Praise."